Well of Being, The : Childhood, Subjectivity, and Education - Kennedy, David, 1943- (Book collections on Project MUSE., 2006)
"In this wide-ranging work, David Kennedy undertakes a philosophically grounded analysis of the history of childhood, the history of adulthood, and their interrelationship. Using themes and perspectives from the history of childhood, mythology, psychoanalysis, art, literature, philosophy, and education, the author locates the experience of childhood across all stages of the human life cycle, and thereby weighs its transformative potential for human culture. He offers a nuanced approach to child study that raises issues about how adults see children and how children see themselves, which could lead to a qualitatively different system of teacher preparation - a system that views the child as participant rather than object in the structure of social reproduction. This sweeping review of conceptions of and approaches to childhood yields a profound vision of what schooling should be like."--Jacket.